THE CONCEPT OF SENSE IN THE QUR'AN: TAZAKKUR, NAZARA, AND TADABBUR AS THE BASIC HUMAN POTENTIAL TOWARDS A SUPERIOR HUMAN BEING - Asrizal Saiin; Mohamad Karuok (QiST: Journal of Quran and Tafseer Studies, 2023)
The position of reason is very important in human life, even the Qur'an also teaches humans to always use their minds correctly and well, so that with good reason, humans will be more noble, moral, moral, educated and valuable compared to other creatures. and benefit both himself and others. Therefore, it is necessary to know the concept of reason contained in the Qur'an, so that with these concepts it will be easier for humans to develop their basic potential to become superior human beings. This research is a type of literature study, the data sources in this study are divided into two, namely primary and secondary. This research is qualitative in nature, in data processing, the authors used descriptive qualitative data analysis techniques with an interpretive approach and with three data analysis methods, namely inductive, deductive, and comparative. The results of the research show that there are three concepts of reason that can be used as basic human potential to become a superior human being directly mentioned in the Qur'an, namely: 1) Tazakkur, 2) Nazara, and 3) Tadabbur. The three concepts of reason according to the Qur'an can be used as development of human potential, especially basic potential. However, there are other concepts of reason that can be used as the basic potential of humans to become superior humans, such as Tafaqquh, Tafakkur, Ta'aqqul, and Fahima. However, these concepts of reason are not mentioned too much repeatedly compared to the three concepts of reason mentioned in this study.